Forensic geropsychology : practice essentials - Bush, Shane S., 1965-; Heck, Andrew L. (American Psychological Association, 2018)
"Geropsychology is a rapidly growing specialty within psychology, with many psychologists assessing and treating older adults in a variety of settings. This book describes aspects of geropsychology in general terms with proposed application to forensic geropsychology. It presents contemporary theory, research, and practice at the intersection of forensic psychology and geropsychology. The book is organized around practice-related issues and forensic contexts. It first describes the relevant ethical issues and common ethical challenges in forensic psychology and offers an approach to maintaining high standards of ethical practice. Then it covers the assessment of response, symptom, and performance validity in forensic geropsychology. The book also covers civil litigation from the perspective of disorders that are commonly the focus of litigation; specifically, traumatic brain injury and its possible causal link to dementia, posttraumatic stress disorder, and pain syndromes. It addresses the assessment and restoration of competency to stand trial and to be executed. The book then presents psychology's involvement in the "not guilty by reason of insanity" defense with older adults and reviews the provision of psychological treatment to incarcerated older adults. It covers administrative contexts, including the assessment of testamentary capacity in older adults, issues surrounding older adult veterans who are pursuing benefits from Veterans Affairs because of psychological problems, and psychology's role in guardianship and conservatorship determinations. Finally, it addresses the mitigating effects of age-related issues on criminal sentencing and housing placements, which are relevant in both criminal and administrative contexts."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)